The whole machinery : the rural modern in cultures of the U.S. South, 1890-1946 - Child, Ben (New southern studies., 2019)
A familiar story holds that modernization radiates out from metropolitan origins. The whole machinery explores representations of people and places, objects and occasions, that reverse that trajectory, demonstrating how modernizing agents move in a contrary direction as well--from the country to city. In a crucial reversal, these figures aren't pulled by or into urban modernity so much as they bring alternate--and transformative--iterations of the modern to the urban world. This book upends the U.S. South's reputation as retrograde and unresponsive to modernity by showing how the effects of national and transnational exchange (particularly via the cotton trade), emergent technologies, and industrialization animate environments and bodies associated with, or performing, versions of the rural. To this end, it also searches out the shadow side of the cosmopolitan modern by investigating the rural sources--the laboring bodies and raw materials--that made such urban spaces possible. The whole machinery explores a range of canonical and noncanonical figures: Paul Laurence Dunbar, Frances E.W. Harper, W.E.B. Du Bois, Allen Tate, Don West, the authors of the Southern Tenant Farmers' Union pamphlet The Disinherited Speak, Charlie Poole, and Zora Neale Hurston among them. It uncovers signs of the rural modern in a variety of texts and media, including narrative fiction and poetry, as well as photographs, sound recordings, radio broadcasts, letters, newspaper reports, and magazine profiles. These readings convey diverse and individuated desires for escape or entrenchment, often in the same conflicted voice, ultimately creating multivalent expressions and experiences of rurality that are, in their way, as thoroughly modern as those of more widely canonized urban figures.